2016
DOI: 10.1039/c6ib00113k
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoscale mechanics guides cellular decision making

Abstract: This study used novel, force-limited nanoscale tension gauges to investigate how force and substrate stiffness guide cellular decision-making during initial cell attachment and spreading on deformable substrates. The well-established dependence of cell traction and spreading on substrate stiffness has been attributed to levels of force exerted on molecular components in focal contacts. The molecular tension gauges used in this study enabled direct estimates of threshold, pico Newton forces that instructed deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A prior study of epithelial cells reported changes in focal adhesion size and area in cells on both 40kPa and 8.8 kPa hydrogels [26]. However, the present study used softer 1.1 kPa gels, and softer substrates are well known to reduce integrin activation and ligand binding [24,48,53]. But VE-cadherin-mediated force transduction activates phospho-inositide-3-kinase, which can activate integrins by inside-out signaling [26].…”
Section: Discussionmentioning
confidence: 94%
“…A prior study of epithelial cells reported changes in focal adhesion size and area in cells on both 40kPa and 8.8 kPa hydrogels [26]. However, the present study used softer 1.1 kPa gels, and softer substrates are well known to reduce integrin activation and ligand binding [24,48,53]. But VE-cadherin-mediated force transduction activates phospho-inositide-3-kinase, which can activate integrins by inside-out signaling [26].…”
Section: Discussionmentioning
confidence: 94%
“…For example, if the link between ligand and substrate cannot sustain sufficient force, cells are unable to adhere independent of the stiffness of the underlying substrate (18). Besides this extreme, binary case, a range of potential force-bearing linkages can exist, which have been shown to affect force loading (19)(20)(21). Moreover, traction force-induced changes in conformation of large ECM proteins such as fibronectin (FN) can alter receptor-ligand engagement and dynamics (22).…”
Section: Introductionmentioning
confidence: 99%
“…Integrin-mediated mechanotransduction occurs via the linkage between integrins binding their ECM ligands and the cytoskeleton through a ~40 nm-high focal adhesion (FA) core [6]. Interaction between ECM–FAs operate at the nanoscale: a nano-mechanical coupling exists between matrix characteristics and integrin-mediated cell adhesion, guiding cell behavior [7]. Therefore, nanopatterned surfaces have been extensively used to study ECM–cell interactions at the nanoscale and to identify the geometric cues that initiate and guide cell adhesion, such as spatial sensing [8], which in turn conditions cell spreading [9], migration [10], and differentiation [11].…”
Section: Introductionmentioning
confidence: 99%